Learning strategies, self-efficacy beliefs and academic achievement of first-year preservice teachers: a person-centred approach - Vilppu Henna; Laakkonen Eero; Laine Anu; Lähteenmäki Marko; Metsäpelto Riitta-Leena; Mikkilä-Erdmann Mirjamaija; Warinowski Anu (Springer, 2025)
As teacher profession can be seen as a learning profession, it is crucial that teacher education equips future teachers with high-level skills to update and increase their proficiency and expertise throughout their career. In this aim, cognitive processing strategies and metacognitive regulation strategies as well as academic self-efficacy beliefs play a crucial role. This study examined Finnish first-year preservice teachers’ (N = 538) initial learning profiles in terms of their learning strategies and self-efficacy beliefs upon entry to teacher education. Furthermore, the association between the profiles and pre-entry factors (age, written entrance exam) as well as first-year achievement was studied. The data were gathered via questionnaire from four universities and their student registers. The person-centred approach utilising a latent profile analysis was applied to identify learning profiles among preservice teachers. Three distinct learning profiles were identified: unregulated students with low self-efficacy (37.5%), average strategists with low self-efficacy (33.1%) and self-regulated and deep learners with high self-efficacy (29.4%). The first profile performed worst in the first-year studies, whereas the last profile was characterised by the oldest students and best performers in the written entrance exam. The findings expand our understanding of the initial learning profiles of preservice teachers and thus offer valuable information for teacher educators to support teaching practices and curriculum design. Practical implications of the results are discussed.